UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA TENTANG IMAN KEPADA QODHO’ DAN QODAR MELALUI METODE BELAJAR AKTIF MODEL MENINJAU KEMBALI KESULITAN MATERI PELAJARAN: DOI: https://doi.org/10.37850/cendekia.v12i1.98 - Ahsanuddin (Cendekia, 2020)
Educators are expected to develop learning methods in accordance with competency standards and basic competencies. Achievement of all the basic competencies of commendable behavior can be done irregularly. The role of all school elements, parents of students and the community is very important in supporting the successful achievement of the objectives of Islamic Education. The purpose of this study was to determine (1) the level of mastery of Islamic Religious Education subject matter on Faith in Qodho and Qodar students (2) the level of mastery of Islamic Religious Education subject matter on Faith in Qodho ’and Qodar that students have received in facing the grade promotion test. From the analysis it was found that student achievement increased from cycle I to II, namely cycle I (68.75%), cycle II (87.50%) students who experienced mastery. From the results of the learning activities that have been carried out for two cycles and based on all the discussions and analyzes that have been carried out it can be concluded as follows Learning with active learning methods models reviewing difficulties in the subject matter of Islamic Religious Education about Faith in Qodho and Qodar has a positive impact in improving learning achievement the student.